Solvent induced miscibility between polymers, and its influence on the morphology, and mechanical properties of their blends. (May 2015) - Marwat, Zafarullah Khan; Baloch, Musa Kaleem
Graphical abstract: Highlights: Morphology showed DMF was better solvent than CHCl3 for compatibility of PS and PSAN. FTIR spectra of PS, PSAN, and their blend films indicated very weak miscibility. PS + PSAN + DMF blends exhibited partial miscibility by displaying two Tg ′ s whose values varied with composition. The partial miscibility was due to weak Van der Waals interactions/entanglements. The mechanical properties of the blend were composition/miscibility dependent. Abstract: Solvent dependent miscibility, morphology, thermal, and mechanical behavior of polystyrene (PS) + poly (styrene-co-acrylonitrile) (PSAN) blend films cast from dimethyl form amide (DMF), and chloroform (CHCl3 ) solvents, were examined by scanning electron microscopy (SEM), Fourier transform infra-red (FTIR) spectroscopy, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and tensile testing techniques. Morphological analyzes revealed better interfacial adhesion between the blend components in DMF than CHCl3 . Almost no signs of miscibility were detected in PS/PSAN blends irrespective of the type of casting-solvent by FTIR probably due to very weak intermolecular interactions. All the blend films, irrespective of the type of solvent, showed two glass transition temperatures that were composition-dependent in the case of PS + PSAN from DMF. However, in the case of PS/PSAN/chloroform blend system, almost all the blend compositions retained the Tg values of their components. The Tg results suggested partial miscibility of the components in the DMF and almost immiscibility in the CHCl3 . Thermal degradation behavior also verified DSC results as PS/PSAN/DMF blend film having composition, 25/75 indicated greater thermal stability than the neat polymers, and other blend compositions. However, in the case of PS + PSAN from chloroform, all the blend compositions were thermally less stable as compared to the neat polymers. Mechanical properties also corroborated SEM, DSC, and TGA results for both the blend systems thereby confirming partial miscibility of PS + PSAN from DMF, and immiscibility of PS + PSAN from chloroform blend systems.